Characterisation and Performance Evaluation of Silica Incorporated Membrane for Wastewater Filtration - SHARMINI FERNANDES, CHARLENE (IRC, 2017)
Membrane technology, such as membrane bioreactors (MBRs) have long been applied for water and wastewater treatment due to its numerous advantages compared to conventional processes. However, the biggest challenge in pressure driven membrane process is membrane fouling. Fouling decreases the productivity and efficiency of the filtration, reduces the membrane lifespan and eventually reduces the efficiency of the processes. In this study, a novel membrane is developed for water based filtration that incorporates silica nanoparticles into polyvinylidene fluoride (PVDF) membrane to improve its structural properties. Adding silica into the membrane matrix does not significantly alter contact angle and membrane pore size. There was an increase in clean water permeability of the membranes and their filterability for treating activated sludge, microalgae solution, secondary effluent and raw sewage as feeds. An increase of silica loading up to 3% increases the pure water permeability by a 125%. We believe that silica acts as an effective pore forming agent that increases the number of pores without significantly altering the pore sizes, as suggested from air permeability data. A higher number of small pores on the surface of the membrane could reduce membrane fouling because of a low specific loading imposed to individual pores.